Development of smart energy meter for energy cost analysis of conventional grid and solar energy - Faisal M.; Karim T.F.; Ridwan Pavel A.; Hossen M.S.; Hossain Lipu M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric measuring instruments; Electric power transmission networks; Electric power utilization; Electric variables measurement; Robotics; Signal processing; Solar energy; Voltage regulators; Controllers; Cost benefit analysis; Microcontrollers; Smart meters; Smart power grids; Conventional grid; Electricity generation; Electricity-consumption; Energy cost; Energy meters; Smart energy meters; Solar charge controller; Voltage transformer; Billing systems; Cost analysis; Electricity-generation; Energy usage; Metering systems; Cost benefit analysis; Solar energy